Comparison of a 20 degree and 70 degree tilt test in adolescent myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) patients - van Campen, C. (Linda) M. C.; Rowe, Peter C.; Visser, Frans C. (Frontiers in Pediatrics, 2023)
Introduction: During a standard 70-degree head-up tilt test, 90% of adults with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) develop an abnormal reduction in cerebral blood flow (CBF). A 70-degree test might not be tolerated by young ME/CFS patients because of the high incidence of syncopal spells. This study examined whether a test at 20 degrees would be sufficient to provoke important reductions in CBF in young ME/CFS patients. Methods: We analyzed 83 studies of adolescent ME/CFS patients. We assessed CBF using extracranial Doppler measurements of the internal carotid and vertebral arteries supine and during the tilt. We studied 42 adolescents during a 20 degree and 41 during a 70 degree test. Results: At 20 degrees, no patients developed postural orthostatic tachycardia (POTS), compared to 32% at 70 degrees (p=0.0002). The CBF reduction during the 20 degree tilt of -27(6)% was slightly less than during a 70 degree test (-31(7)%; p=0.003). Seventeen adolescents had CBF measurements at both 20 and 70 degrees. The CBF reduction at 70 degrees was significantly larger than at 20 degrees (p<0.0001). Conclusions: A 20 degree tilt in young ME/CFS patients resulted in a CBF reduction comparable to that in adult patients during a 70 degree test. The lower tilt angle provoked less POTS, emphasizing the importance of using the 70 degree angle for that diagnosis. Further study is needed to explore whether CBF measurements during tilt provide an improved standard for classifying orthostatic intolerance.